2013
DOI: 10.1111/str.12040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tensile Fracture Behaviours of Selected Aluminum Alloys under Various Loading Conditions

Abstract: Experiments investigating dynamic tensile fracture were performed on the extruded rods of 2024‐T4 and 7075‐T6 aluminum alloys under varying loading conditions. The initial yield stress and fracture strain of 7075‐T6 alloy obtained in spilt Hopkinson tension bar tests are higher than that of 2024‐T4 alloy. But the initiation fracture toughness and spall strength of 2024‐T4 alloy are higher than those of 7075‐T6 alloy in three‐point bending and plate impact experiments, which indicates that 2024‐T4 alloy has bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Kowalewski et al, 2014;Szusta and Seweryn, 2017), dynamic (e.g. Kumar et al, 2011;Wang et al, 2013), creep (and relaxation) (e.g. Lumley et al, 2002;Lin et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Kowalewski et al, 2014;Szusta and Seweryn, 2017), dynamic (e.g. Kumar et al, 2011;Wang et al, 2013), creep (and relaxation) (e.g. Lumley et al, 2002;Lin et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic tensile fracture (or spall) behaviours of metallic materials produced by the interaction of release waves after shock loading is a complicated physical process that can be strongly influenced by many variables related to the applied loading, temperature, and the material itself . A number of researchers have studied how the spall behaviour of materials depends on the loading conditions . In fact, accurate determinations of these microstructural effects on a material's spall behaviour are important for the development of structure‐property correlations, better alloy design for improved properties, and predictive material damage models.…”
Section: Introductionmentioning
confidence: 99%
“…Also, MacMaster and colleagues obtained the fracture toughness of 6061-T6 Al alloy as 48.7 [33]. Lastly, Wang et al revealed that the 7075-T6 Al alloy has a fracture toughness of 33 [34]. The experimental findings in the literature were utilized as reference values, and Figure 7 was generated.…”
Section: Discussionmentioning
confidence: 99%